Restricted Additive Schwarz Preconditioner for Elliptic Equations with Jump Coefficients (Advances in Applied Mathematics and Mechanics, 2021)
This paper provides a proof of robustness of the restricted additive Schwarzpreconditioner with harmonic overlap (RASHO) for the second order elliptic problemswith jump coefficients. By analyzing the eigenvalue distribution of the RASHO preconditioner,we prove that the convergence rate of preconditioned conjugate gradientmethod with RASHO preconditioner is uniform with respect to the large jump andmesh size.